Hindu Nationalism and Governance/edited by John McGuire and - "McGuire, John (ed.)" (New Delhi, 2007)
The volume assembles some of the best-known analysts as also emerging talent in the study of Indian politics and especially Hindu nationalist politics. It focuses on governance under the BJP government in India across areas such as political alliances, performance in elections, economic reforms and privatization, food security, ideology, revisionist histories, religion, nationalism and the media.
Keywords: Politics